The use of Antibiotics in Paediatric Dentistry: A Revision of Current Recommendations - Piekoszewska-Ziętek, Paula (The Journal of Dentists, 2022)
Antibiotics are commonly used in medicine and dentistry for both preventive and therapeutic reasons. They are most widely prescribed medications in paediatric dentistry. According to the literature, approximately 7-11% of antibiotic therapy is prescribed by dentists. The most commonly used are β-lactam antibiotics, macrolides, tetracyclines, clindamycin, metronidazole. Unrestricted use of antibiotics is a cause of growing bacterial resistance. The aim of the study was to review the literature for the clinical indications, dosages, and duration of antibiotic therapy in the field of peadiatric dentistry. The author reviewed the scientific literature and for evidence regarding the use of antibiotics to prevent local and systemic infections associated with dental treatment in children. Actual recommendations and clues for clinician are provided in this article.